Her only wish [large type] - Gray, Shelley Shepard (Gray, Shelley Shepard. Season in Pinecraft, 2023)
"Betsy Detweiler is on a mission to get out of Kentucky and experience new things. What better place to start than with her friends in Pinecraft, Florida? From the moment Betsy walks into the Snow Bird Golf Course to sign up for lessons, August Troyer is mesmerized. Betsy is beautiful yet awkward, outgoing yet unsure, joyful yet hesitant. She's like no one he's ever met before. As Betsy and August embark on a month of enjoying life to the fullest, they encounter several reasons to play it safe. But playing it safe has its own consequences. This tender romance reminds us that life and love require a fair amount of risk." -- Provided by publisher.